A Improving Vocaional Skill in Making Banana Bolen Through Explicit Instruction Method for Mil Metally Impaired Student - Sunyi Angelista; Johandri Taufan (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study is to improve vocational skills in making banana bolen through the Explicit Instruction method for two mild mentally retarded students in SLB N 2 Padang Class XI. This type of research is classroom action research which is carried out in two cycles. Cycle I consisted of four meetings and cycle II consisted of three meetings. The stages of each cycle are planning, action,observation and reflection stages. The results of the study showed that there was an increase in students' ability to make banana ballen. The percentage of initial ability RA 40.67%. In the first cycle increased to 65.11% and 97.67% in the second cycle. Meanwhile, in child R, the initial condition was 41.86%. Padang cycle I experienced an increase of 66.27% and cycle II to 96.51%. It can be concluded that the explicit instruction method can improve the vocational ability to make banana bolen for mild mentally retarded children in class XI at SLB N 2 Padang.